Evidence‐Based Use of Perioperative Antibiotics in Otolaryngology. (6th February 2018) - Patel, Priyesh N.; Jayawardena, Asitha D. L.; Walden, Rachel L.; Penn, Edward B.; Francis, David O.
Abstract : Objective: To identify and clarify current evidence supporting and disputing the effectiveness of perioperative antibiotic use for common otolaryngology procedures. Data Sources: PubMed, Embase (OVID), and CINAHL (EBSCO). Review Methods: English‐language, original research (systematic reviews/meta‐analyses, randomized control trials, prospective or retrospective cohort studies, case‐control studies, or case series) studies that evaluated the role of perioperative antibiotic use in common otolaryngology surgeries were systematically extracted using standardized search criteria by 2 investigators independently. Conclusions: Current evidence does not support routine antibiotic prophylaxis for tonsillectomy, simple septorhinoplasty, endoscopic sinus surgery, clean otologic surgery (tympanostomy with tube placement, tympanoplasty, stapedectomy, and mastoidectomy), and clean head and neck surgeries (eg, thyroidectomy, parathyroidectomy, salivary gland excisions). Antibiotic prophylaxis is recommended for complex septorhinoplasty, skull base surgery (anterior and lateral), clean‐contaminated otologic surgery (cholesteatoma, purulent otorrhea), and clean‐contaminated head and neck surgery (violation of aerodigestive tract, free flaps). In these cases, antibiotic use for 24 to 48 hours postoperatively has shown equal benefit to longer duration of prophylaxis. Despite lack of high‐quality evidence, the US Food and Drug Administration suggests antibiotic prophylaxis for cochlear implantation due to the devastating consequence of infection. Data are inconclusive regarding postoperative prophylaxis for nasal packing/splints after sinonasal surgery. Implications for Practice: Evidence does not support the use of perioperative antibiotics for most otolaryngologic procedures. Antibiotic overuse and variability among providers may be due to lack of formal practice guidelines. This review can help otolaryngologists understand current evidence so they can make informed decisions about perioperative antibiotic usage.